THE ANALYSIS OF STRATEGIC MANAGEMENT AT CIPTO MANGUNKUSUMO HOSPITAL AS A TEACHING HOSPITAL, UNIVERSITAS INDONESIA - Agustina, Oviani; Safaria, Dra. Siti (UTSAHA: Journal of Entrepreneurship, 2023)
The effectiveness in improving academic quality in universities is determined by good and practical management. Universities must have a quality management strategy to provide high-quality education. Therefore, this research aims to analyze the activities that occur at the Universitas Indonesia in improving the quality of its management that facilitates students’ both academic and non-academic activities. This research is a descriptive qualitative approach that focus to observe and analyze existing strategies at the Faculty of Medicine, Universitas Indonesia. This research also provides the recommendations for alternative strategies to achieve a competitive advantage. This research is using data analysis from interviews and formulating business strategies through 3 steps. The result of this research is in Medicine faculty of Universitas Indonesia already has a good corporate branding as an opportunity to increase promotion; develop more aggressive advertising; adjusting the market share for growing; and become more loyal in the term of  service and quality of the Medicine faculty of Universitas Indonesia.